Limited seed dispersal may explain differences in forest colonization by the Japanese raisin tree (Hovenia dulcis Thunb.), an invasive alien tree in Southern Brazil - Dechoum, Michele (2015)
The Japanese raisin tree (Hovenia dulcis) is an invasive tree in South American forests, which produces capsuled fruits attached to peduncles that grow thick and fleshy when ripe. Frugivorous birds have been cited as dispersal agents of H. dulcis. The spread of H. dulcis propagules to non-invaded sites was evaluated at a local spatial scale in deciduous forests in Southern Brazil, in order to propose management strategies to prevent the arrival of propagules of such species in non-invaded sites. Seed arrival by birds was assessed by installing five 0.6 x 0.6 m seed traps in each 10 x 10 m plots installed in non-invaded sites at different distances from invaded sites. Seed arrival was also compared between control plots and plots where all H. dulcis trees were felled within a 30m radius from the center of plots. A limitation in short distance seed dispersal by birds was observed in the study area. There was a negative exponential relationship between number of seeds and distance from H. dulcis trees to non-invaded sites and a positive exponential dependence of the number of seeds found in seed traps on the basal area of H. dulcis. The felling of H. dulcis trees was effective in reducing the arrival of seeds in non-invaded sites, resulting in a significantly smaller number of seeds in managed plots than in control plots.